Perception And Response of Islamic Religious Education Teachers to Religious Education Policy During the Covid-19 Pandemic - Abdul Adzim; Faris Khoirul Anam (Universitas Yudharta Pasuruan, 2020)
This study aims to determine the perceptions and responses of Islamic Religious Education teachers to educational policies during the COVID-19 pandemic. The results of this study provide an overview of technical policy making in educational units. Government policy towards the implementation of Islamic education raises pros and cons in society. This study shows that Islamic religious education teachers in public schools and colleges have different responses to online learning. 70% of Islamic Religious Education teachers said that they agreed with government policies in an effort to tackle the COVID-19 pandemic. However, 24% of them said that this policy seemed forced on all sectors of education. The interesting thing revealed in this study is that Islamic Religious Education teachers have a high level of optimism towards the government regarding overcoming the COVID-19 pandemic in Indonesia. This study used a qualitative model with in-depth interviews with 9 Islamic Religious Education teachers at 4 schools of various levels. The interview instrument was previously validated by an expert